Przesłanki zawieszenia organów gminy i ustanowienia zarządu komisarycznego - Masternak-Kubiak, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The institution of supervision over the activity of territorial self-government is the basic institution of the public legal order, that defines the limits of independence of local governments’ units. It defines the real scope of freedom of action of the local governments. The art. 171 para. 1 of the Constitution of the Republic of Poland states that all activities of territorial self-governments are supervised based on only on the aspect of legality. This means that the authorised supervisory body may examine the activities of the local government unit only in order to check if they are compliant with the universally binding law. The supervisory authorities may interfere with the activities of the local government when the law has been violated and they are not authorised to assess the efficacy, diligence and economic prudence of the activities taken by the local government. The Prime Minister, while suspending the local government bodies, is also obliged to establish the receivership. These are the inseparable actions, i.e. there is no suspension of the local government bodies without the establishment of the receivership. The clue of this measure of supervision is the appointment of the government commissioner, while the suspension of the local government bodies is only a prerequisite for making this decision.
Keywords: Constitution; legality; local government; supervision; Prime Minister; act; receivership; statute